2022
DOI: 10.3390/cancers14143531
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Shows a Better Efficacy Than Endocrine Therapy in Metastatic Breast Cancer Patients with a Heterogeneous Estrogen Receptor Expression Assessed by 18F-FES PET

Abstract: Background: The heterogeneity of estrogen receptor (ER) expression has long been a challenge for the diagnosis and treatment strategy of metastatic breast cancer (MBC). A novel convenient method of ER detection using 18F-fluoroestradiol positron emission tomography/computed tomography (18F-FES PET/CT) offers a chance to screen and analyze MBC patients with ER uncertainty. Methods: MBC patients who received 18F-FES PET/CT were screened and patients with both FES positive (FES+) and negative (FES-) lesions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…A retrospective study of 56 patients with known ER+ metastatic breast cancer who underwent FES PET/CT before combined endocrine and palbociclib (cyclin-dependent kinase 4/6-inhibitor) therapy found that patients with only FES-positive lesions had a substantially longer progression-free survival compared to those ER+ breast cancer patients who had at least one FES-negative lesion (23.6 months compared to 2.4 months) [ 45 ]. Similarly, a retrospective study of 75 patients with ER+ metastatic breast cancer found that patients with ER heterogeneity (both FES-positive and FES-negative lesions) responded better to chemotherapy than endocrine therapy, and did not improve with combined chemotherapy and endocrine therapy [ 46 ]. The utility of FES to guide clinical management can be especially useful in patients who have both ER+ breast cancer and at least one other primary malignancy.…”
Section: Estrogen Receptormentioning
confidence: 99%
“…A retrospective study of 56 patients with known ER+ metastatic breast cancer who underwent FES PET/CT before combined endocrine and palbociclib (cyclin-dependent kinase 4/6-inhibitor) therapy found that patients with only FES-positive lesions had a substantially longer progression-free survival compared to those ER+ breast cancer patients who had at least one FES-negative lesion (23.6 months compared to 2.4 months) [ 45 ]. Similarly, a retrospective study of 75 patients with ER+ metastatic breast cancer found that patients with ER heterogeneity (both FES-positive and FES-negative lesions) responded better to chemotherapy than endocrine therapy, and did not improve with combined chemotherapy and endocrine therapy [ 46 ]. The utility of FES to guide clinical management can be especially useful in patients who have both ER+ breast cancer and at least one other primary malignancy.…”
Section: Estrogen Receptormentioning
confidence: 99%
“…All studies were published between 1995 and 2022, 6,7,10-14,18-53 of which 29 (63%) were prospective. 6,7,[10][11][12][13][14][18][19][20][21][23][24][25][26][27][28][29]34,36,[43][44][45][46][47][48][49][50][51] Of the 43 studies, 32 (74%) were on breast cancer, 6,7,[18][19][20][21][22][23][24][25][26]28,31,[33][34][35][37][38][39][40][41][43][44]…”
Section: Results Basic Characteristics Of Included Studies and Patientsmentioning
confidence: 99%
“…Of the 43 included studies, 28 (63%) conducted FES PET imaging to detect ER expression on malignant lesions, 6,7,[10][11][12][20][21][22][23][24][25][27][28][29][31][32][33][34][35][36][37][38][39][40][41]46,52 and 12 (28%) 13,24,39,41,42,[45][46][47][48][49][50][51] and 4 (9%) 14,43,44,53 studies conducted FES PET imaging, respectively, to predict and monitor the treatment response (such as endocrine therapy or chemotherapy), progressionfree survival (PFS), and overall survival (OS) (Table 1).…”
Section: Results Basic Characteristics Of Included Studies and Patientsmentioning
confidence: 99%
“…Furthermore, multiple potential clinical applications for 18 F-FES PET have been proposed, including selecting patients for hormonal therapy, solving clinical dilemmas and systemic staging of tumors with low metabolic activity (10). In terms of prediction of therapeutic response, study had shown that patients with ER heterogeneity or uncertainty tumors on 18 F-FES PET showed better sensitivity to chemotherapy rather than endocrine therapy (29). In another trial evaluating tumor heterogeneity by 18 F-FES PET as a predictive marker in MBC patients receiving palbociclib combined endocrine therapy, nine out of ten patients with an FES-negative site developed PD, with a median PFS of only 2.4 months.…”
Section: Discussionmentioning
confidence: 99%